Spirit of Vedanta Ushering Hinduism to The Idea of Universalism (Discourse on Swami Vivekananda’s Thought) - Abdullah MuslichRizal Maulana; Sufratman Sufratman; Syafira Anisatul Izah (Journal of Comparative Study of Religions (JCSR), 2020)
In itsdevelopment, Hinduism experienced many changes to its modern era. Apart from all its traditions, Hinduism tries to introduce its existence on the world stage. Reformers of modern Hinduism such as Sri Ramakrishna, Rammohun Roy, and Swami Vivekananda themselves contributed greatly to this new idea with their respective models of practice. Departing from Swami Vivekananda attending the World Religious Parliament in Chicago in 1893, he brought the vision of his spiritual teacher Sri Ramakrishna about the Harmony of Religions are true. In the Parliament, he upheld his Vedanta teachings, which have been reinterpreted according to his Ideal concept, that Vedanta is the teaching of the future. Based on its Universal concept, Vedanta is able to take the World’s attention to its teaching in the West. In an effort to realize this idea, 1897, Swami Vivekananda disseminated the religious message of his teacher by establishing the Ramakrishna Mission, an organization to strengthen and expand the Vedanta idea. Since its inception, the Ramakrishna Mission has been dedicated to improving spiritually and social service, as well as developing religious teachings.